EP275 Cervical cancer screening in africa: a proposal of a different combination of VIA test and PAP smear in uganda. (1st November 2019) - Corrado, G; Mazzara, C; Certelli, C; Nsubuga, JB; Zanetto, F; Schurfeld, K; Dell'Antonio, G; Dagli Orti, C; Oryono, A; Andriani, T
Abstract : Introduction/Background: AFRON Oncology for Africa is an Italian non-profit organization that works for female cancer prevention in the Sub-Saharan area, mainly in Uganda. Although the visual inspection with acetic acid (VIA) is one of the most widespread screening method in African countries, it did not show a high accuracy. The aim of this study is to evaluate the efficacy and usefulness of VIA test combined with the PAP smear in Uganda in order to find possible solutions that may be used in a low-resource setting. Methodology: Between January 2011 and October 2018, eight screening campaigns were held in Kampala, Kitgum and Karamoja. In the last two campaigns, we decided to try a new approach: we performed the PAP smear before the VIA test and, in case of a positive VIA test, we sent the slide for examination. To compare them, we divided the data collected in two groups: the first five campaigns (2011–2016), in which a standard approach was used, and the last two campaigns (2017–2018), in which the new approach was used. Results: During the study period, 9, 780 women were screened (median age 34), of whom 699 were positive at the VIA test. The VIA test showed 584 (83.5%) false positives. In the first group, the VIA test was positive in 516 women, of whom 483 (93%) were referred for further examinations. In the second group, in which the VIA test was positive in 173 women, the PAP smear was positive in 46 of the 173 slides analysed. Thus, only 46 of the 173 (26.5%) women were referred for further examinations. Conclusion: Combining the PAP smear, VIA test and slide analysis in positive VIA tests may allow women who need treatment to be selected more effectively, while waiting for other more expensive solutions to become more affordable and suitable for these settings. Disclosure: Nothing to disclose.